Importance Of Research As A Subject In Hospitality Undergraduate Courses (PUSA Journal of Hospitality and Applied Sciences, 2017)
Background: Research is an important and essential part of any industry or institution. It helps  in discovering new ground breaking facts about existing subjects and systems. Research is an  important part of undergraduate curriculum. Objective: To understand the importance of research  as a subject in hospitality under-graduate courses. Methodology: Data was collected by means  of a questionnaire which was filled by the hospitality undergraduate students (n=200). Results: The findings of the study revealed that 76 % of respondents accepted that research is an important  subject for undergraduate, 54% respondent accepted its benefits in skill developments. Among all  respondents only 21% respondents showed interest in becoming researchers in future. Overall the  students felt the importance of the subject. However, very few showed interest in pursuing research  as a career. Conclusion: There is a need to sensitize students to increase the awareness and promote  research not only as a subject but as a culture.
Keywords: Research; Researcher; Academic Importance; Personal and Social Enhancement